2018
DOI: 10.1080/02670844.2016.1259096
|View full text |Cite
|
Sign up to set email alerts
|

A study of laser cladding NiCrBSi/Mo composite coatings

Abstract: Laser cladding Ni-based composite coating was fabricated on the surface of 42CrMo steel using 6 kW fibre laser. By the addition of Mo powder, a well-formed and crack-free laser cladding composite coating was obtained. The morphology, composition, microhardness and wear resistance of composite coatings were studied using a scanning electron microscopy, an energy-dispersive spectroscopy, an X-ray diffraction spectrum, a microhardness tester and a wear tester. The results show that the cladding layer has metallur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Moreover, there also exists an increased industrial demand for all the components with higher performance and durability [ 11 ]. Therefore, it is imperative to repair and reconstruct the worn and damaged components in order to extend the life span and minimize waste of expensive materials, economic losses, downtime, and embodied energy, thereby increasing the industrial competitiveness [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there also exists an increased industrial demand for all the components with higher performance and durability [ 11 ]. Therefore, it is imperative to repair and reconstruct the worn and damaged components in order to extend the life span and minimize waste of expensive materials, economic losses, downtime, and embodied energy, thereby increasing the industrial competitiveness [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 demonstrates the EDS mapping of the laser cladded Ni45 + 40 wt.% high-carbon ferrochrome coating, which exhibits that the concentrations of Cr and C were higher in the lath-shaped structures. As known, nickel alloys with chromium, boron, and silicon contents represent a type of hard facing alloys by means of the formation of nickel, chromium borides and complex carbides as dominant primary hard phases [13,14]. In this paper, high-carbon ferrochrome was added to the Ni45 alloy, and as a result more chromium carbides could form due to the high Cr content of high-carbon ferrochrome.…”
Section: Experimental Materials and Proceduresmentioning
confidence: 99%
“…It was found that a good metallurgical bonding was formed between the substrate and the cladding layer; additionally, there were few pores and cracks, which indicated the rationality of the method. Because the growth of the crystal morphology during solidification mainly depends on the value of G/R [9], where 'G' means the temperature gradient of the liquid phase and 'R' is the solidification rate of solid phase, the instantaneous value of G/R changes with the distance to the solidification interface. The cladding layer is divided into three parts: bottom, middle and top, each having a different micro-morphology [24,25].…”
Section: Microstructure Of Coatingmentioning
confidence: 99%
“…At present, Fe-based [1][2][3], Ni-based [4,5], and Co-based [6,7] self-fluxing alloy powders are widely used to repair and strengthen the surface performance in laser cladding. The mechanical properties of coatings are analyzed through microhardness, wear resistance and microstructure properties, and the results shows that coatings can be equal to, or even superior to those of the alloys fabricated by die-casting or forging [8,9]. The repair and recycle industries are therefore greatly enhanced by the advances in laser cladding technology, and have widespread applications in many fields, such as petroleum, chemical, and military [10][11][12].…”
Section: Introductionmentioning
confidence: 99%